The Effect of Smoking on Some Liver Enzymes in the City of Diwaniyah - Mohammad, Nargis Sadiq; Hmood, Khadeeja Abees (American Journal of Biology and Natural Sciences, 2025)
The results indicated the effect of smoking on liver enzymes. A significant increase (P<0.01) was observed for each enzyme ALT, AST, and ALP compared with the control group. However, the GGT enzyme did not show significant differences. Regarding the effect of the type of smoking on liver enzymes, a significant increase (P<0.05) was observed for each of the ALP and AST enzymes, and the highest concentration was in hookah smokers, respectively, compared to the control group. However, the GGT and ALT enzymes did not show significant differences.